Valoración de la economía circular en la gestión de residuos sólidos por estudiantes de la Institución Educativa San Marcos, Iquitos – Loreto, 2025 - Guzman Nuñez, Barbara Lucero (2025)
This study, with a quantitative approach and a non-experimental, cross-sectional, and correlational design, evaluated the levels of environmental knowledge, attitudes, dispositions, and practices of 40 students from 3rd to 5th grade of secondary school at the San Marcos Educational Institution in 2025, using census sampling. A structured 17-item survey was used, with a reliability level of 0.755 (Cronbach's alpha). Descriptive analysis allowed characterizing the responses, and since normality was not found in the data (Shapiro-Wilk test), Spearman's Rho coefficient was applied for inferential analysis. The results reveal that, while most students recognize the principles of the circular economy (reduce, reuse, and recycle), there is a weak disposition toward sustainable practices such as waste separation and support for recycling programs. Uncertainty was also observed regarding the applicability of the approach in the school context. Institutional infrastructure, although equipped with separate bins, is insufficient due to its inadequate location and lack of signage and educational programs. Environmental mitigation measures and training are significantly related to compliance with environmental regulations, unlike supervision and monitoring. Overall, the findings highlight the need to strengthen pedagogical strategies and improve material conditions to promote an active and engaged environmental culture among students.